A culture of ambiguity: an alternative history of Islam - Bauer, Thomas (Columbia University Press, 2021)
1. Introduction -- 2. Cultural Ambiguity -- 3. Does God Speak in Textual Variants? -- 4. Does God Speak Ambiguously? -- 5. The Blessing of Dissent -- 6. The Islamization of Islam -- 7. Language: A Serious Business and a Game -- 8. The Ambiguity of Sexual Desire -- 9. The Serene Look at the World -- 10. In Quest of Certainty -- Bibliography.